2019
DOI: 10.1037/tps0000199
|View full text |Cite
|
Sign up to set email alerts
|

Modeling trauma to develop treatments for posttraumatic stress.

Abstract: Posttraumatic stress disorder (PTSD) is a chronic mental health disorder that impairs daily functioning and reduces overall quality of life. Current treatments are effective only in some patient populations and do not adequately address all aspects of PTSD’s complex symptomatology. This is largely attributable to current gaps in knowledge about the pathophysiology of the disorder. Animal models of PTSD are a critical part of the drug discovery process. Animal models of PTSD use intense stressors to model traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 276 publications
(362 reference statements)
0
3
0
Order By: Relevance
“…In general, individuals in military, police, or other first responder jobs can be exposed to major, frequent, or prolonged stressful events throughout the course of their employment. We know from animal-based research that all of these types of events can elicit stress and or/PTSD-like responses, which likely explains the prevalence of this disorder category within the OSI population [13]. PTSD involves one or more traumatic events (traumas) that are experienced, witnessed, or learned about by the person exposed to them [11].…”
Section: Trauma-and Stressor-related Disordersmentioning
confidence: 99%
“…In general, individuals in military, police, or other first responder jobs can be exposed to major, frequent, or prolonged stressful events throughout the course of their employment. We know from animal-based research that all of these types of events can elicit stress and or/PTSD-like responses, which likely explains the prevalence of this disorder category within the OSI population [13]. PTSD involves one or more traumatic events (traumas) that are experienced, witnessed, or learned about by the person exposed to them [11].…”
Section: Trauma-and Stressor-related Disordersmentioning
confidence: 99%
“…Animal models have been integral to the understanding of the effects of a variety of stress exposures on neurophysiological and neurobehavioral processes [22]. Many models rely on one form of stress presented in a single exposure or over repeated exposures to provoke measurable responses, typically behavioral, endocrine, or physiological in nature.…”
Section: Development Of Medications For Operational Use In the Far Te...mentioning
confidence: 99%
“…As reviewed in the current special issue, animal models have provided a breadth of knowledge related to neurodevelopmental and psychiatric disorders involving substance use and dependence, deregulated impulse control and motivated behaviors, stress related pathophysiology, and intervention targets (Bale et al, 2019). In the current issue, Lowery-Gionta et al (2019) highlight that links between proinflammatory markers and posttraumatic stress disorder (PTSD) in humans are currently under study in animal models suggesting previously unrealized connections between the neuroimmune axis and PTSD-like behavioral outcomes. In addition, preclinical studies in animal models have identified potential therapeutic targets for PTSD treatment across multiple neurochemical systems.…”
mentioning
confidence: 99%